Effects of nerve growth factor experimentally-induced craniofacial muscle sensitization on referred pain frequency and number of headache days: A double-blind, randomized placebo-controlled study. (December 2018) - Exposto, FG; Masuda, M; Castrillon, EE; Svensson, P
Objective: To assess if repeated intramuscular injections of nerve growth factor into the temporalis and masseter muscles increase mechanical sensitivity and entropy scores. Furthermore, to investigate if increased mechanical sensitivity would lead to increased prevalence of referred pain in the studied individuals. Finally, if increased muscle sensitization would lead to an increase in number of headache days during the experimental period. Methods: The present double-blind, randomized placebo-controlled study recruited 16 healthy participants who were injected with nerve growth-factor, on 2 days, into the masseter and temporalis muscles and isotonic saline on the contralateral side. Mechanical sensitivity was assessed at seven different time-points (total of 21 days) by application of three different forces to 15 different sites of both muscles. Participants were asked after each force application if they experienced referred pain and were asked to keep a headache diary during the experimental period. Results: In summary, a) repeated intramuscular injections of nerve-growth-factor caused an increase in mechanical sensitivity for the masseter but not the temporalis muscle, and an increase in entropy scores when compared to the isotonic saline side. b) Both referred pain frequency and number of headache days were not increased following nerve-growth-factor injections. Conclusions: These findings support the idea that mechanical sensitization in the masseter and temporalis muscles differs following injections of nerve growth factor. Furthermore, referred pain and headache frequency do not seem to be related to nerve growth factor sensitization in this model. These findings support the idea that in healthy individuals referred pain may be an epiphenomenon of the muscle in response to noxious input.